(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2023)
The article addresses the issue of human talent management indicators, with the purpose of demonstrating which indicators allow organizations to establish strategies, so that their personnel are trained and can adapt to changing circumstances, as well as achieve the goals established by the company, the object of study was descriptive analysis, with information analyzed from various sources. The analyzed results show how to implement the appropriate indicators to evaluate the performance of each worker and identify the contribution they make within the company, in order to improve their performance. In conclusion, the management indicators help to strengthen the behavior of the personnel and establish strategies. . that will allow companies with good elements that are suitable and have the skills and talents necessary to achieve the goals of the organization to be more competitive.